Addressing Participation with Early Inflammatory Arthritis: Insights into the Lived Experience and Exploring a Clinical Model to Address Participation Restrictions - Codd, Yvonne (Trinity College Dublin. School of Medicine. Discipline of Occupational Therapy, 2021)
The focus of this multiphase study is exploring the impacts of inflammatory arthritis on participation and engagement in life roles, and how clinical services address client-identified participation restrictions associated with this disease. A sequential mixed methods study design with a qualitative priority was employed to address the study aims. Phase one utilised an anonymous online descriptive survey, using convenience sampling, to explore rheumatology team members' perspectives on the delivery of work-based participation supports in rheumatology services for inflammatory arthritis. Phase two employed one-off focus groups with service providers to describe and explore multidisciplinary-led early arthritis clinics as a model for addressing participation in newly diagnosed inflammatory arthritis. The final phase of the study comprised individual interviews with service users attending multidisciplinary-led early arthritis clinics to explore the impacts of newly diagnosed inflammatory arthritis on participation, and how client-identified participation and engagement impacts were addressed in the multidisciplinary-led early arthritis clinics. Phase one online survey findings were analysed descriptively, and data gathered from the open-ended questions were analysed using basic content analysis. A qualitative description framework was used in phase two and three of the study and purposive sampling was employed for both qualitative phases. Qualitative data from phases two and three were analysed using thematic analysis methodologies. Study findings emphasise the extensive and diverse impact of inflammatory arthritis on participation, early in the disease trajectory. Participation-based restrictions were widely reported and pervasive across all life roles and various life stages, and were described in the areas of employment, home-based roles, life-partner relationships, parenting, leisure, and social roles. Altered capacity was identified as directly impacting on self-identity, well-being, and quality of life. Role switch was recognised as a natural consequence of early inflammatory arthritis but was consistently emphasised as having a negative impact on well-being and self-identity. Findings highlighted addressing the occupation-based participation impacts associated with inflammatory arthritis is an important part of the management of this condition. Participants in this study emphasised their need for early interventions to manage these early participation restrictions and they identified occupation-based interventions as a priority for their healthcare. Findings identified the extensive impact of inflammatory arthritis on work, and the consequential need for work-participation supports for this population, however variances in how these identified work-based difficulties are being managed were identified. In traditional approaches rheumatology clinicians are not directive in asking about employment-based restrictions, and they tend to rely on the client to name work concerns. Use of gatekeeper approaches to identifying work-based participation difficulties appears to be unsuitable as rheumatology clinicians do not have the time, expertise of resources to explore work-based participation issues and a lack of clarity regarding the optimum time for work referral and types of work support contribute to dissatisfaction with traditional approaches. Conversely, the multidisciplinary-led early arthritis clinic model, was identified as providing a coordinated approach to effectively manage work-based problems. Findings emphasised that the explicit focus on work participation within the multidisciplinary-led service provided clarity and a clear process to identify and manage work-based issues which significantly contributed to both service providers' and service users' satisfaction with how work issues were addressed. Findings indicate that the multidisciplinary-led early arthritis model is a clinical management approach which addresses participation and engagement. This model provides automatic, easy, and early access to support for service users to identify and manage the occupation-based participation restrictions associated with early inflammatory arthritis and is aligned with best practice guidelines. Furthermore, the model provides a full multidisciplinary team who work collaboratively and in an interdisciplinary way, to deliver supports and interventions to address the early impacts of inflammatory arthritis on body structures, function, and participation and engagement. An explicit emphasis on participation combined with a 'right advice, in the right way and at the right time' approach was identified as the most influential features of the delivery of this model in supporting positive health outcomes and occupational adaptation. The collaborative approach utilised in the multidisciplinary-led early arthritis model contributes to the strength of addressing participation needs, however expansive qualitative evidence identified that participation interventions and supporting engagement are optimally located within the domain of occupational therapy.
APPROVED
Keywords: Participation; Early Inflammatory Arthritis; Client-identified Participation Restrictions; Qualitative Description; Healthcare Delivery; Multidisciplinary Team Approach; Employment; Life Roles; Occupational Identity